Corruption, Development and the Environment - Pellegrini, Lorenzo; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
The book analyses the influence of corruption on economic growth and environmental protection, examining corruption from different perspectives. It contributes to several streams of the literature and assembles evidence of the influence of corruption on two important variables in human welfare: income and environmental policies. The material evinces the detrimental effect that corruption has on economic growth and on the stringency of environmental policies. It also shows that standard techniques for fighting corruption are often based either on simplistic definitions or on strong assumptions that do not apply in many countries blighted by corruption. From a methodological standpoint, this work combines a number of approaches including a theoretical discussion of corruption and of its definition (often omitted in economic studies), together with econometrics, case studies and policy discussions.
1. Introduction -- 2. Economic Analysis of Corruption -- 3. Causes of Corruption: A Curvey of Cross-Country Analyses and Extended Results -- 4. The Effect of Corruption On Growth and Its Transmission Channels -- 5. Corruption, Democracy and Environmental Policy: An Empirical Contribution To The Debate -- 6. Corruption and Environmental Policies: What Are the Implications For the Enlarged EU?- 7. The Rule of the Jungle In Pakistan: A Case Study On Corruption and Forest Management In Swat -- 8. Conclusions and Future Research -- Subject/Author Index.
Keywords: Economics; Sustainable development; Pollution; Development Economics; Economic policy; Europe -- Economic policy; Environmental economics; Economics/Management Science; Environmental Economics; Development Economics; Economic Policy; Sustainable Development; Pollution, general; European Integration